Revealing hole trapping in zinc oxide nanoparticles by time-resolved X-ray spectroscopy - Penfold, Thomas J.; Szlachetko, Jakub; Santomauro, Fabio G.; Britz, Alexander; Gawelda, Wojciech; Doumy, Gilles; March, Anne Marie; Southworth, Stephen H.; Rittmann, Jochen; Abela, Rafael; Chergui, Majed; Milne, Christopher J. (Nature communications, 2018)
Nanostructures of transition metal oxides, such as zinc oxide, have attracted considerable interest for solar-energy conversion and photocatalysis. Both applications are sensitive to the transport and trapping of photoexcited charge carriers. The probing of electron trapping has recently become possible using time-resolved element-sensitive methods, such as X-ray spectroscopy. However, valence-band-trapped holes have so far escaped observation. Herein we use X-ray absorption spectroscopy combined with a dispersive X-ray emission spectrometer to probe the charge carrier relaxation and trapping processes in zinc oxide nanoparticles after above band-gap photoexcitation. Our results, supported by simulations, demonstrate that within 80 ps, photoexcited holes are trapped at singly charged oxygen vacancies, which causes an outward displacement by ~15% of the four surrounding zinc atoms away from the doubly charged vacancy. This identification of the hole traps provides insight for future developments of transition metal oxide-based nanodevices. Metal-oxide nanostructures are used in a range of light-driven applications, yet the fundamentals behind their properties are poorly understood. Here the authors probe photoexcited zinc oxide nanoparticles using time-resolved X-ray spectroscopy, identifying photocatalytically-active hole traps as oxygen vacancies in the lattice.